PENYELEKSI PRODUK CACAT MINUMAN KEMASAN - kusumastuti, sri kusumastuti (ReTII, 2019)
Separation of defective products in the industry is needed so that the quality of circulating products in the market is guaranteed quality. An error in the production of bottled drinks that may occur is the presence of bottled water that has not been filled. Separation of defective products that have been done manually by workers allows errors to occur due to fatigue. To prevent this in this study, designing and making an automated tool for separating defective products in beverage packaging using the Programable Logic Controller (PLC). Bottles that have not been filled with drinking water running on the conveyor will be detected by the proximity sensor capacitive. Packaging data from the capacitive proximity sensor is shifted in memory by the Shift program instructions, each photoelectric sensor detects the presence of packaging that runs on a conveyor. At a certain position, data from packages that have not been filled with drinking water are used as an electric solenoid valve pneumatic command activating the cylinder / piston to separate the defective product from the disposal site.Keyword : product selection, PLC, sensor